I'm still alive - Saviano, Roberto, 1979- (Archaia, 2022)
"In this devastating and resilient graphic memoir, Saviano shares his experiences of witnessing the power and violence of the Camorra firsthand and the nightmarish anxieties of living under armed guard, all while courageously continuing to call attention to the deeply rooted crime and corruption that plagues not only his hometown, but also many Italian and foreign cities where criminal organizations have stretched their tentacles."--cover page 4